1978
DOI: 10.1530/acta.0.0870768
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for a Different Response of Red and White Skeletal Muscle of the Rat in Different Thyroid States

Abstract: The influence of thyroid hormone depletion and experimental hyperthyroidism on red and white skeletal muscle of the rat during periods of 2, 4 and 8 weeks were studied. Body weight, muscle weight, mitochondrial protein content, and specific activities of the mitochondrial enzymes \g=a\-glycerophosphatedehydrogenase (EC 1.1.99.5) (\g=a\-GPD) and succinate dehydrogenase (EC 1.3.99.1) (SDH) were used as parameters. The largest differences in body weight gain and muscle weight gain (both red and white muscle) in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
13
2

Year Published

1981
1981
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 9 publications
5
13
2
Order By: Relevance
“…Conversely, no change was found in the extensor digitorum longus (EDL) [11,123], a white muscle mainly composed of fast-twitch glycolitic fibres (Type IIb). These results are consistent with early observations that red, but not white muscles, are sensitive to thyroid hormones [124,125]. Lipid peroxidation was also increased by thyroid hormone in rat gastrocnemious [110,126], a mixed fibre muscle also containing fast-twitch oxidative glycolytic fibers (type IIa), but was decreased in the white portion of such a muscle [12].…”
Section: Oxidative Stress In Experimental Hyperthyroidism and Hypothysupporting
confidence: 92%
“…Conversely, no change was found in the extensor digitorum longus (EDL) [11,123], a white muscle mainly composed of fast-twitch glycolitic fibres (Type IIb). These results are consistent with early observations that red, but not white muscles, are sensitive to thyroid hormones [124,125]. Lipid peroxidation was also increased by thyroid hormone in rat gastrocnemious [110,126], a mixed fibre muscle also containing fast-twitch oxidative glycolytic fibers (type IIa), but was decreased in the white portion of such a muscle [12].…”
Section: Oxidative Stress In Experimental Hyperthyroidism and Hypothysupporting
confidence: 92%
“…Studies have shown that after 4-6 wk of hypothyroidism due to thyroidectomy, biochemical and physiological changes occur in muscles (4, 9, 15). Body weight increased only slightly to 245±10 g during this 2-mo period (normal rats gained 100-150 g during the same time), a feature consistant with other studies of rat hypothyroidism (8). Serum T4 levels were undetectable at the time of NMR testing (normal 6.05+±1.55 Mg/dl, ±2 SD, n = 16).…”
Section: Animalssupporting
confidence: 78%
“…Furthermore, the activities of several key mitochondrial enzymes are reduced (4)(5)(6)(7)(8)(9). The latter is more pronounced in slow twitch, red muscles compared with fast, white muscles (7,8). Oxidative metabolism of these transformed fibers should be less efficient in hypothyroidism, yet Wiles et al (10, 1 1) found diminished fatigability in human hypothyroid muscles.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…1971) who found that doses of250 jug ofT3/kg body weight for 8 days resulted in an increase in mitochondrial cz-glycerophosphate dehydrogenase in the soleus muscle of the rat while no change could be detected in the rectus femoris, a muscle made of mostly f.g. fibres. Janssen, van Hardeveld & Kassenaar (1978) also found that 2 weeks of T4 administration was enough to increase the activities of mitochondrial aglycerophosphate and succinate dehydrogenase in 'red' muscle while no changes were found in 'white' muscle even after 4 weeks of treatment. The results of Winder et al (1975) could be due to the fact that they used muscles with heterogeneous fibre populations and the responses of some other fibre types to thyroid hormones could have been masked by the lack of response of some other fibre types.…”
Section: Fibre Compositionmentioning
confidence: 85%